Correction: Spiral Eu(III) coordination polymers with circularly polarized luminescence - Hasegawa, Yasuchika; Miura, Yui; Kitagawa, Yuichi; Wada, Satoshi; Nakanishi, Takayuki; Fushimi, Koji; Seki, Tomohiro; Ito, Hajime; Iwasa, Takeshi; Taketsugu, Tetsuya; Gon, Masayuki; Tanaka, Kazuo; et al. (Chemical communications (Cambridge, England), 2025)
Correction for 'Spiral Eu(III) coordination polymers with circularly polarized luminescence' by Yasuchika Hasegawa et al., Chem. Commun., 2018, 54, 10695-10697, https://doi.org/10.1039/C8CC05147J.Correction for 'Spiral Eu(III) coordination polymers with circularly polarized luminescence' by Yasuchika Hasegawa et al., Chem. Commun., 2018, 54, 10695-10697, https://doi.org/10.1039/C8CC05147J.